Complete genome sequence of cherry virus T, a novel cherry-infecting tepovirus - Marais, A; Šafářová, D; Navrátil, M; Faure, C; Cornaggia, D; Brans, Y; Suchá, J; Candresse, T (Archives of virology, 2020)
Double-stranded RNA and total RNA purified from sour cherry leaves (Prunus cerasus, cv. Amarelka Chvalkovicka) was analyzed by high-throughput sequencing. BLAST annotation identified contigs with homology to several already known cherry-infecting viruses (prune dwarf virus, prunus necrotic ringspot virus, prunus virus F, little cherry virus 1) as well as contigs with sequences more distantly related to those of members of the family Betaflexiviridae and in particular to prunus virus T of the genus Tepovirus. The full genome sequence of a putative virus (6,847 nucleotides [nt]; GenBank no. MT090966) was assembled and completed at the genome ends. The genome has a typical tepovirus organization, containing three overlapping open reading frames (ORFs), encoding a replication-associated protein, a movement protein and a capsid protein, respectively. Both its genome organization and its phylogenetic relationships show that the virus belongs to the genus Tepovirus, but considering the species demarcation criteria for the family Betaflexiviridae, it appears to represent a novel virus species, and we propose the name "cherry virus T" (ChVT) for this virus.
Keywords: sekvenování celého genomu; nemoci rostlin; Phylogeny; Open Reading Frames; Prunus avium; sekvence nukleotidů; Plant Diseases; genom virový; Base Sequence; Flexiviridae; Whole Genome Sequencing; otevřené čtecí rámce; Genome, Viral; fylogeneze; vysoce účinné nukleotidové sekvenování; High-Throughput Nucleotide Sequencing